(untitled) (Economic studies journal, 2020)
The study aimed to identify indicators of knowledge economy in Libya from data published by international organizations and institutions, whether indicators of education and development or indicators of economic incentives and Regulatory Quality. The study concluded that the weak and delayed indicators of the knowledge economy in Libya and their non-impact on the economic growth based mainly on oil production and export. The study recommended the need for an advanced educational system, an environment conducive to scientific research and facilitating an enabling environment for the structural transformation of the knowledge economy in terms of macroeconomic policies, business environment and Regulatory Quality